(untitled) (Research, Society and Development, 2021)
BCC is the most common non-melanoma skin tumor in Brazil and also the most benign, with small metastatic capacity and relative potential for local tissue destruction. It originates from basal cells of the epidermis and also from different parts of the follicular apparatus that have undergone chronic action of ultraviolet radiation. The study was justified due to the importance of BCC in the current medical scenario, as this condition is recurrent and can cause numerous losses to the patient, whether organic or psychosocial. Therefore, it requires better therapeutic methodology and early screening. 65-year-old male ACCA patient comes to the dermatological office with at least five skin lesions characteristic of BCC that have evolved for more than 10 years in frontooccipital regions (0.5x0.3 cm), pinna (1.5x1.0 cm) ), upper limbs (0.7x0.4 cm) and two on the anterior side of the right lower limb (1.0x0.6 cm). Refers to family and personal history of recurrent skin tumors and reports living social stigma resulting from the disease. Surgical excision with free margins and primary closure was performed, except in the leg region, in which skin grafting from the groin region was performed with Brown’s dressing. The sample of biological material collected was subjected to a histopathological study that proved the diagnostic hypothesis of BCC in varying degrees of differentiation. Currently, he is undergoing dermatological follow-up to follow the wound healing and reports satisfaction with the result obtained. BCC frequently appears in dermatological clinics and medical clinics as the main complaint of patients with a history of chronic photoexposure or with a family history of skin tumors requiring surgical treatment. It is important to encourage the habit of solar photoprotection, as well as the search for professionals trained in the early diagnosis of the disease in order to avoid both the onset and evolution of this condition and the need for extensive surgical intervention and the compromise of the patient’s self-esteem.